2016
DOI: 10.1038/eye.2016.164
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with stereopsis and a good visual acuity outcome among children in the Infant Aphakia Treatment Study

Abstract: Purpose To identify factors associated with stereopsis in children with good visual acuity after unilateral congenital cataract surgery in the Infant Aphakia Treatment Study. Patients and methods Infants with a unilateral congenital cataract (n = 114) were randomized to IOL implantation or contact lens correction after cataract surgery. At age 4.5 years, a masked examiner assessed HOTV acuity and stereopsis. Adherence to patching was assessed using 48-h recall telephone interviews and 7-day diaries throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…Numerous studies have been conducted to investigate how to reduce the incidence of strabismus in children with unilateral congenital cataract and some have suggested that patching the dominant eye for long periods reduces the risk of developing strabismus while others advocate that reduced patching hours improves stereopsis (10). A retrospective study, including patients of the Infant Aphakia Treatment Study (IATS), suggested that patching 4 h/day during the rst year of life, 3 h/day from 1-3 years and 2 h/day at age 4 increased the chances of good visual acuity and stereopsis (11). Compared to other studies, we found a similar incidence of strabismus and nystagmus among patients with congenital cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted to investigate how to reduce the incidence of strabismus in children with unilateral congenital cataract and some have suggested that patching the dominant eye for long periods reduces the risk of developing strabismus while others advocate that reduced patching hours improves stereopsis (10). A retrospective study, including patients of the Infant Aphakia Treatment Study (IATS), suggested that patching 4 h/day during the rst year of life, 3 h/day from 1-3 years and 2 h/day at age 4 increased the chances of good visual acuity and stereopsis (11). Compared to other studies, we found a similar incidence of strabismus and nystagmus among patients with congenital cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Early removal of congenital cataracts is essential to stop deprivation of vision during the sensitive and critical period of vision development [7]. There are a few options that can be undertaken to correct the resulting aphakia; primary intraocular lens (IOL) implantation, the use of spectacles or contact lenses, or secondary IOL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…One-half of the children in the IATS with 20/40 or better vision had measurable stereopsis whereas stereopsis was rare in children with vision worse than 20/40. 18,19 Second, children with better vision in their treated eye may be more adherent with treatment regimens in general. We have previously reported an association between good patching adherence and better visual acuity in the treated eye.…”
Section: Discussionmentioning
confidence: 99%